MORTALITY PREDICTORS OF PATIENTS UNDERGOING CORONARY ARTERY BYPASS GRAFT SURGERY - Kunal Patel; Kavin Raj; Avleen Kaur; Monil Majmundar; Harshvardhan Zala; Vyoma Patel; Pratik Patel (Elsevier, 2023)
Therapeutic Area: Mortality risk assessment after CABG Background: Advanced liver disease is a risk factor for cardiac surgery. However, liver dysfunction is not included in cardiac risk assessment models for patients undergoing coronary artery bypass graft surgery (CABG). Limited number of studies have reported perioperative outcomes of CABG in cirrhotic patients so far. We sought to study the mortality predictors of patients who underwent CABG including cirrhotic patients with cirrhosis. Methods: Using the National Inpatient Sample database, we identified patients who underwent CABG from 2016 to 2018 in the United States. We used multivariate logistic regression model to calculate odds ratio for in-patient mortality predictors. Results: We identified a total of 605,864 CABG admissions of which in-hospital mortality occurred in 2.4% (95% CI 2.3-2.5) of patients. Patients with cirrhosis had 3.37 times higher odds of mortality (95% CI 2.49-4.56). Age, female gender, heart failure, stroke, vascular disease, chronic pulmonary disease, metastatic cancer, and chronic kidney disease had higher odds of mortality after CABG. Elective admission, hypertension and diabetes had lower odds of in-hospital mortality after CABG. Atrial fibrillation and blood loss anemia did not have statistically significant association with in-hospital mortality. Conclusion: In conclusion, patients with cirrhosis have a higher rate of in-hospital mortality. The presence of cirrhosis should be taken into consideration along with traditional cardiac risk assessment models before selecting the ideal approach to revascularization.